CuBTC / PAN composite nanofiber adsorption film as well as preparation method and application thereof

The CuBTC/PAN composite nanofiber membrane effectively addresses the inefficiencies of existing absorbent materials by enhancing surface area and interaction sites, achieving superior adsorption of SF6/N2 decomposition products like SO2F2 and NF3, thus improving insulation performance and reducing device size.

CN119633768APending Publication Date: 2025-03-18GUIZHOU POWER GRID CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411593963.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Current absorbent materials used in the power industry, such as metal oxides and activated carbons, are ineffective in capturing SF6/N2 mixture decomposition products like SO2F2 and NF3, leading to reduced insulation performance and increased device size, failing to meet the demand for efficient handling of these gases.

Method used

A CuBTC/PAN composite nanofiber membrane is developed through a method involving the synthesis of copper-based metal-organic framework (CuBTC) and polyacrylonitrile (PAN) nanofibers, where CuBTC is dispersed onto PAN nanofibers using a spraying technique, enhancing the membrane's surface area and adsorption capacity.

Benefits of technology

The CuBTC/PAN composite nanofiber membrane exhibits improved adsorption performance, achieving 17mmol/g for SO2F2 and 10mmol/g for NF3 under specific conditions, effectively addressing the inefficiencies of existing materials by increasing surface area and interaction sites for gas molecules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633768A_ABST
    Figure CN119633768A_ABST
Patent Text Reader

Abstract

The invention discloses a CuBTC / PAN composite nanofiber adsorption film and a preparation method and application thereof. The preparation method comprises the steps that copper salt and dimethyl sulfoxide are mixed, heated and stirred to obtain a metal salt solution; heating, stirring, separating, washing, heating and drying the organic ligand and a metal salt solution to obtain CuBTC precipitate; mixing polyacrylonitrile with dimethylformamide to obtain a faint yellow transparent viscous liquid, and carrying out electrostatic spinning to obtain a polyacrylonitrile nanofiber membrane; mixing the CuBTC precipitate with isopropanol, and performing ice-bath ultrasonic dispersion to obtain dark blue dispersion liquid; and spraying the dark blue dispersion liquid on the surface of the polyacrylonitrile nanofiber membrane, and drying to obtain the CuBTC / PAN composite nanofiber adsorption membrane. According to the present invention, the requirement of the good adsorption effect on the SF6 / N2 mixed gas decomposition components SO2F2 and NF3 is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nitrogen trifluoride and sulfuryl fluoride capture and separation, and specifically relates to a CuBTC / PAN composite nanofiber adsorption membrane and a preparation method and application thereof. Background Art

[0002] Sulfur hexafluoride (SF6) gas is a colorless, odorless, non-toxic and non-flammable inert gas. Its excellent insulation and arc extinguishing properties have been widely used in the power industry. Among them, gas-insulated combined switchgear has the advantages of easy maintenance, long service life and small footprint, so it is widely used in ultra-high voltage power systems.

[0003] In actual operation, SF6 is often mixed with N2. However, under long-term high-voltage operation, discharge or overheating may occur inside the equipment, directly causing SF6 gas to decompose to varying degrees, and react with trace oxygen and moisture to form decomposition products such as sulfur dioxide (SO2), nitrogen trifluoride (NF3), sulfinyl fluoride (SOF2) and sulfuryl fluoride (SO2F2), which will reduce the insulation strength of SF6 gas and endanger the stability of the power system. Moreover, if these toxic gas products are directly discharged into the atmosphere, they will also pose a threat to human health. Therefore, in order to ensure the long-term operation of the equipment, it is very important to treat the waste gas of the decomposition components of the SF6 / N2 mixed gas.

[0004] Among them, the adsorption materials currently used in the power industry are mainly metal oxides (such as activated alumina), activated carbon (fiber), zeolite / carbon molecular sieve, etc. However, there are a series of problems such as poor adsorption effect leading to decreased insulation performance of gas media and increased equipment footprint, which cannot meet the current demand for adsorbing the decomposition components of SF6 / N2 mixed gas, SO2F2 and NF3. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a CuBTC / PAN composite nanofiber adsorption membrane.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a CuBTC / PAN composite nanofiber adsorption membrane, characterized in that: comprising:

[0009] The copper salt and dimethyl sulfoxide are mixed and heated and stirred to obtain a metal salt solution;

[0010] The organic ligand and the metal salt solution are heated, stirred, separated, washed, heated, and dried to obtain a CuBTC precipitate;

[0011] Polyacrylonitrile and dimethylformamide were mixed to obtain a light yellow transparent viscous liquid, which was electrospun to obtain a polyacrylonitrile nanofiber membrane;

[0012] The CuBTC precipitate was mixed with isopropanol and then dispersed ultrasonically in an ice bath to obtain a dark blue dispersion;

[0013] The CuBTC / PAN composite nanofiber adsorption membrane is obtained by spraying the dark blue dispersion on the surface of the polyacrylonitrile nanofiber membrane and then drying it.

[0014] As a preferred embodiment of the preparation method of the present invention, the copper salt includes one or more of copper chloride, copper nitrate and copper acetate.

[0015] As a preferred embodiment of the preparation method of the present invention, the organic ligand is trimesic acid.

[0016] As a preferred embodiment of the preparation method of the present invention, the addition ratio of the organic ligand to the metal salt solution is 1-1.5:2.5-3.

[0017] As a preferred embodiment of the preparation method of the present invention, the addition ratio of polyacrylonitrile to dimethylformamide is 1-1.2:0.8-1.

[0018] As a preferred embodiment of the preparation method described in the present invention, the electrospinning conditions are as follows: electrospinning is carried out at a flow rate of 2 ml / h under a voltage of 18 kV, the rotation speed of the drum collector is set to 160 r / min, the movement speed of the reciprocating platform is set to 900 mm / min, the distance between the needle and the drum is set to 15 cm, tin foil is used as the receiving substrate, the spinning environment temperature is controlled at 25°C, the relative humidity is controlled at 30%, and the time is 7.5 h.

[0019] As a preferred embodiment of the preparation method of the present invention, the addition ratio of the CuBTC precipitate to isopropanol is 0.8-1.2:18-22.

[0020] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a CuBTC / PAN composite nanofiber adsorption membrane to obtain a CuBTC / PAN composite nanofiber adsorption membrane.

[0021] As a preferred embodiment of the CuBTC / PAN composite nanofiber adsorption membrane of the present invention, the CuBTC / PAN composite nanofiber adsorption membrane has an adsorption capacity of 17 mmol / g for SO2F2 single gas and an adsorption capacity of 10 mmol / g for NF3 single gas under the environment of 150 kPa and 298 k.

[0022] As a preferred embodiment of the CuBTC / PAN composite nanofiber adsorption membrane of the present invention, the CuBTC / PAN composite nanofiber adsorption membrane can achieve an adsorption capacity of 12 mmol / g for SO2F2 and 3 mmol / g for NF3 mixed gas of the same concentration.

[0023] Another object of the present invention is to overcome the deficiencies in the prior art and provide a CuBTC / PAN composite nanofiber adsorption membrane for use in adsorbing decomposition products of a mixed gas of sulfur hexafluoride and nitrogen.

[0024] Beneficial effects of the present invention:

[0025] (1) The composite fiber membrane formed by the metal organic framework CuBTC and the porous substrate prepared by the present invention has the advantages of larger specific surface area, more metal active sites, etc. Among them, CuBTC is a porous structure with good adsorption performance, and the porous substrates are interwoven with each other with high specific surface area and large porosity, which not only provides more contact sites for CuBTC, but also promotes the adsorption of gas molecules, thereby accelerating the electron exchange speed between CuBTC as a sensitive material and gas molecules, but also helps the penetration and diffusion of gas molecules, thereby significantly improving the gas sensitivity and adsorption effect of the adsorption material. In addition, combining the metal organic framework with the easy-to-process nanofiber material can form a specific structure that is easy to integrate, that is, it has excellent processing potential and mechanical properties.

[0026] (2) In simulated tests, the adsorption material prepared by the present invention can achieve an adsorption amount of 17 mmol / g for SO2F2 single gas and 10 mmol / g for NF3 single gas under the environment of 150 kPa and 298 kPa. Under the same conditions, the adsorption amount of 50 mmol / g of SO2F2 and NF3 mixed gas can reach 12 mmol / g for SO2F2 and 3 mmol / g for NF3, which meets the demand for better adsorption effect on the decomposition components of SF6 / N2 mixed gas, SO2F2 and NF3. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0028] Figure 1 This is a scanning electron microscope image of the CuBTC / PAN composite nanofiber adsorption membrane of Example 1 of the present invention.

[0029] Figure 2 The adsorption curves of the adsorption materials of Examples 1, 2, 3 and Comparative Example 1 of the present invention for single gas components SO2F2 and NF3 are shown.

[0030] Figure 3 The adsorption curves of the adsorption materials of Examples 1, 2, 3 and Comparative Example 1 of the present invention for the mixed gas components of SO2F2 and NF3 are shown. DETAILED DESCRIPTION

[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0033] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0034] Unless otherwise specified, all raw materials used in the examples of the present invention are commercially available, as shown in Table 1 for details.

[0035] Table 1

[0036]

[0037] Example 1

[0038] (1) Dissolve 0.5 g of copper nitrate trihydrate in 3.8 ml of dimethyl sulfoxide (concentration: 1.1 g / mL) and heat at 40° C. with stirring until completely dissolved to form a metal salt solution;

[0039] 0.25 g of trimesic acid (BTC) ligand was added to the metal salt solution, and the solution was heated and stirred at 40° C. for 3 h to allow BTC to fully react with copper ions.

[0040] In this process, the carboxylic acid group of BTC forms a coordination bond with the copper ion, gradually generating a precursor of CuBTC. The reaction temperature, reaction time and pH value of the solution are controlled to gradually convert the precursor into CuBTC precipitation, wherein the reaction temperature is 30°C, the reaction time is 10h and the pH value is 7.

[0041] The CuBTC precipitate is separated from the solution using filter paper or a centrifuge and washed with deionized water to remove excess reagents and impurities attached to the surface of the precipitate. The washed CuBTC precipitate is heated to 60°C in an oven and dried for 24 hours to remove residual moisture and solvent to obtain the final CuBTC product.

[0042] (2) 1.7 g of polyacrylonitrile (PAN) particles were added to 15 mL of DMF, then transferred to a 20 mL sample bottle and stirred at room temperature for 12 h using a magnetic stirrer to obtain a uniform light yellow transparent PAN viscous liquid as a precursor for electrospinning;

[0043] The solution was transferred to a 20 mL syringe using a 22G flat-head needle. Electrospinning was performed at a flow rate of 2 ml / h at a voltage of 18 kV. The rotation speed of the drum collector was set to 160 r / min, the speed of the reciprocating platform was set to 900 mm / min, the distance between the needle and the drum was set to 15 cm, tin foil was used as a receiving substrate, the spinning environment temperature was controlled at 25 °C, the relative humidity was controlled at 30%, and the PAN nanofiber membrane was obtained after spinning for 7.5 h.

[0044] (3) Synthesis of PAN-MOFs composite nanofiber membrane by spray doping method: 500 mg CuBTC product was added into a 20 mL sample bottle containing 12 mL isopropyl alcohol (IPA), stirred at room temperature for 0.5 h using a magnetic stirrer, and then ultrasonically dispersed in an ice bath at 750 W power using an ultrasonic disperser for 2 h to obtain a uniform dark blue dispersion;

[0045] The dispersion was loaded into a pneumatic spray gun, and the speed of the drum loaded with PAN nanofiber membrane was set to 180 r / min. The CuBTC particles were sprayed reciprocatingly at a vertical distance of 5 cm and a horizontal range of 10 cm from the membrane surface to evenly load the CuBTC particles on the surface of the PAN nanofiber membrane. After spraying, the composite membrane was removed and placed in an 80°C oven for drying for 12 hours to remove excess solvent and activate the pores of the CuBTC particles (dried at 300°C for 4 hours) to obtain a CuBTC / PAN composite nanofiber adsorption membrane.

[0046] Example 2

[0047] The difference from Example 1 is that in step (1), copper nitrate trihydrate is substituted for copper chloride.

[0048] (1) Dissolve 0.3 g of copper chloride in 3.8 ml of dimethyl sulfoxide (concentration: 1.1 g / mL) and heat at 35°C with stirring until completely dissolved to form a metal salt solution;

[0049] 0.28 g of trimesic acid (BTC) ligand was added to the metal salt solution, and the solution was heated and stirred at 35° C. for 3 h to allow BTC to fully react with copper ions.

[0050] In this process, the carboxylic acid group of BTC forms a coordination bond with the copper ion, gradually generating a precursor of CuBTC. The reaction temperature, reaction time and pH value of the solution are controlled to gradually convert the precursor into CuBTC precipitation, wherein the reaction temperature is 30°C, the reaction time is 10h and the pH value is 7.

[0051] The CuBTC precipitate is separated from the solution using filter paper or a centrifuge and washed with deionized water to remove excess reagents and impurities attached to the surface of the precipitate. The washed CuBTC precipitate is heated to 80°C in an oven and dried for 18 hours to remove residual moisture and solvent to obtain the final CuBTC product.

[0052] (2) 1.7 g of polyacrylonitrile (PAN) particles were added to 15 mL of DMF, then transferred to a 20 mL sample bottle and stirred at room temperature for 12 h using a magnetic stirrer to obtain a uniform light yellow transparent PAN viscous liquid as a precursor for electrospinning;

[0053] The solution was transferred to a 20 mL syringe using a 22G flat-head needle. Electrospinning was performed at a flow rate of 2 ml / h at a voltage of 18 kV. The rotation speed of the drum collector was set to 160 r / min, the speed of the reciprocating platform was set to 900 mm / min, the distance between the needle and the drum was set to 15 cm, tin foil was used as a receiving substrate, the spinning environment temperature was controlled at 25 °C, the relative humidity was controlled at 30%, and the PAN nanofiber membrane was obtained after spinning for 7.5 h.

[0054] (3) Synthesis of PAN-MOFs composite nanofiber membrane by spray doping method: 500 mg CuBTC product was added into a 20 mL sample bottle containing 12 mL isopropyl alcohol (IPA), stirred at room temperature for 0.5 h using a magnetic stirrer, and then ultrasonically dispersed in an ice bath at 750 W power using an ultrasonic disperser for 2 h to obtain a uniform dark blue dispersion;

[0055] The dispersion was loaded into a pneumatic spray gun, and the speed of the drum loaded with PAN nanofiber membrane was set to 180 r / min. The CuBTC particles were sprayed reciprocatingly at a vertical distance of 5 cm and a horizontal range of 10 cm from the membrane surface to evenly load the CuBTC particles on the surface of the PAN nanofiber membrane. After spraying, the composite membrane was removed and placed in an 80°C oven for drying for 12 hours to remove excess solvent and activate the pores of the CuBTC particles (dried at 300°C for 4 hours) to obtain a CuBTC / PAN composite nanofiber adsorption membrane.

[0056] The effect achieved by the composite nanofiber adsorption membrane of this embodiment is experimentally carried out under the same conditions as the embodiment, that is, in the simulated test, under the environment of 150kPa and 298k, the adsorption amount of SO2F2 single gas can reach 17.5mmol / g, and the adsorption amount of NF3 single gas can reach 10.8mmol / g. Under the same conditions, the adsorption amount of SO2F2 and NF3 mixed gas of 50mmol / g can reach 11.5mmol / g and 3.2mmol / g.

[0057] Example 3

[0058] The difference from Example 1 is that in step (3), the ratio of CuBTC metal frame and isopropanol is modified, thereby changing the proportion of the metal frame of the CuBTC / PAN composite nanofiber membrane.

[0059] (1) Dissolve 0.5 g of copper nitrate trihydrate in 3.8 ml of dimethyl sulfoxide (concentration: 1.1 g / mL) and heat at 40° C. with stirring until completely dissolved to form a metal salt solution;

[0060] 0.25 g of trimesic acid (BTC) ligand was added to the metal salt solution, and the solution was heated and stirred at 40° C. for 3 h to allow BTC to fully react with copper ions.

[0061] In this process, the carboxylic acid group of BTC forms a coordination bond with the copper ion, gradually generating a precursor of CuBTC. The reaction temperature, reaction time and pH value of the solution are controlled to gradually convert the precursor into CuBTC precipitation, wherein the reaction temperature is 30°C, the reaction time is 10h and the pH value is 7.

[0062] The CuBTC precipitate is separated from the solution using filter paper or a centrifuge and washed with deionized water to remove excess reagents and impurities attached to the surface of the precipitate. The washed CuBTC precipitate is heated to 60°C in an oven and dried for 24 hours to remove residual moisture and solvent to obtain the final CuBTC product.

[0063] (2) 1.7 g of polyacrylonitrile (PAN) particles were added to 15 mL of DMF, then transferred to a 20 mL sample bottle and stirred at room temperature for 12 h using a magnetic stirrer to obtain a uniform light yellow transparent PAN viscous liquid as a precursor for electrospinning;

[0064] The solution was transferred to a 20 mL syringe using a 22G flat-head needle. Electrospinning was performed at a flow rate of 2 ml / h at a voltage of 18 kV. The rotation speed of the drum collector was set to 160 r / min, the speed of the reciprocating platform was set to 900 mm / min, the distance between the needle and the drum was set to 15 cm, tin foil was used as a receiving substrate, the spinning environment temperature was controlled at 25 °C, the relative humidity was controlled at 30%, and the PAN nanofiber membrane was obtained after spinning for 7.5 h.

[0065] (3) Synthesis of PAN-MOFs composite nanofiber membrane by spray doping method: 600 mg CuBTC product was added into a 20 mL sample bottle containing 20 mL isopropyl alcohol (IPA), stirred at room temperature for 1 h using a magnetic stirrer, and then ultrasonically dispersed in an ice bath at 750 W power using an ultrasonic disperser for 2 h to obtain a uniform dark blue dispersion;

[0066] The dispersion was loaded into a pneumatic spray gun, and the speed of the drum loaded with PAN nanofiber membrane was set to 180 r / min. The CuBTC particles were sprayed reciprocatingly at a vertical distance of 5 cm and a horizontal range of 10 cm from the membrane surface to evenly load the CuBTC particles on the surface of the PAN nanofiber membrane. After spraying, the composite membrane was removed and placed in an 80°C oven for drying for 12 hours to remove excess solvent and activate the pores of the CuBTC particles (dried at 300°C for 4 hours) to obtain a CuBTC / PAN composite nanofiber adsorption membrane.

[0067] The effect achieved by the composite nanofiber adsorption membrane of this embodiment is experimentally carried out under the same conditions as the embodiment, that is, in the simulated test, under the environment of 150kPa and 298k, the adsorption amount of SO2F2 single gas can reach 17.3mmol / g, and the adsorption amount of NF3 single gas can reach 10.5mmol / g. Under the same conditions, the adsorption amount of SO2F2 and NF3 mixed gas of 50mmol / g can reach 12.2mmol / g and 2.8mmol / g.

[0068] Comparative Example 1

[0069] Comparative Example 1 uses the currently commercially available SF6 circuit breaker adsorption material 4A molecular sieve (model M102749).

[0070] Example 4

[0071] The composite fiber membrane prepared in Example 1 was characterized by scanning electron microscopy (SEM). Figure 1 It can be seen that the fibers in the composite fiber membrane are interlaced to form a polyacrylonitrile porous substrate. With the polyacrylonitrile porous substrate as a support, CuBTC grows uniformly and stably on the porous substrate.

[0072] The adsorption material prepared in this embodiment was placed in a stainless steel adsorption chamber at room temperature, and the gas of the SF6 / N2 decomposition components was filled to 0.15MPa. The adsorption experiment was performed at room temperature. Gas collection and component detection were performed every 5 days, for a total of 4 groups, with a total duration of 20 days. Figure 2 The single gas time-concentration curves of SO2F2 and NF3 obtained from the adsorbent material in Example 1 are: Figure 3 This is the response curve of the adsorbent material obtained in Example 1 to the concentration of the mixed gas of SO2F2 and NF3.

[0073] from Figure 2 It can be seen from the figure (the left is the embodiment, the right is the comparative example 1) that the concentrations of the two gases in the adsorbent material of the embodiment 1 decrease significantly with the increase of time. Figure 2 It can also be seen that the adsorption effect of the adsorbent material of Example 1 on SO2F2 is better than that on NF3 at room temperature. Figure 3 (The left is the embodiment, and the right is comparative example 1) It can be seen that in the adsorption of the mixed gas of SO2F2 and NF3 by the adsorption material of embodiment 1 at room temperature, the adsorption of NF3 will promote the adsorption of SO2F2, and both have obvious adsorption effects, which can meet the adsorption of SO2F2 and NF3, and can be applied to the adsorption material of characteristic decomposition components of SF6 / N2 mixed gas.

[0074] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a CuBTC / PAN composite nanofiber adsorption membrane, characterized in that: include, The copper salt and dimethyl sulfoxide are mixed and heated and stirred to obtain a metal salt solution; The organic ligand and the metal salt solution are heated, stirred, separated, washed, heated, and dried to obtain a CuBTC precipitate; Polyacrylonitrile and dimethylformamide were mixed to obtain a light yellow transparent viscous liquid, which was electrospun to obtain a polyacrylonitrile nanofiber membrane; The CuBTC precipitate was mixed with isopropanol and then dispersed ultrasonically in an ice bath to obtain a dark blue dispersion; The CuBTC / PAN composite nanofiber adsorption membrane is obtained by spraying the dark blue dispersion on the surface of the polyacrylonitrile nanofiber membrane and then drying it.

2. The preparation method according to claim 1, characterized in that: The copper salt includes one or more of copper chloride, copper nitrate and copper acetate; the mass ratio of the copper salt to dimethyl sulfoxide is 1-1.2:3.2-4.

3. The preparation method according to claim 1, characterized in that: The organic ligand is trimesic acid; the addition ratio of the organic ligand to the metal salt solution is 1-1.5:2.5-3.

4. The preparation method according to claim 1, characterized in that: The addition ratio of polyacrylonitrile to dimethylformamide is 1-1.2:0.8-1.

5. The preparation method according to claim 1, characterized in that: The electrospinning conditions are as follows: electrospinning is carried out at a flow rate of 2 ml / h at a voltage of 18 kV, the rotation speed of the drum collector is set to 160 r / min, the speed of the reciprocating platform is set to 900 mm / min, the distance between the needle and the drum is set to 15 cm, tin foil is used as the receiving substrate, the spinning environment temperature is controlled at 25°C, the relative humidity is controlled at 30%, and the time is 7.5 h.

6. The preparation method according to claim 1, characterized in that: The addition ratio of the CuBTC precipitate to isopropanol is 0.8-1.2:18-22.

7. The CuBTC / PAN composite nanofiber adsorption membrane prepared by the preparation method according to claims 1 to 6.

8. The CuBTC / PAN composite nanofiber adsorption membrane according to claim 7, characterized in that: The CuBTC / PAN composite nanofiber adsorption membrane has an adsorption capacity of 17 mmol / g for SO2F2 single gas and an adsorption capacity of 10 mmol / g for NF3 single gas under an environment of 150 kPa and 298 k.

9. The CuBTC / PAN composite nanofiber adsorption membrane according to claim 8, characterized in that: The CuBTC / PAN composite nanofiber adsorption membrane has an adsorption capacity of 12 mmol / g for SO2F2 and NF3 mixed gas of 50 mmol / g, and an adsorption capacity of 3 mmol / g for NF3.

10. Use of the CuBTC / PAN composite nanofiber adsorption membrane as claimed in claim 9 in adsorbing decomposition products of a mixed gas of sulfur hexafluoride and nitrogen.